Site-specific herbicide splitting in field carrots based on camera detected weed infestation - Dammer, Karl-Heinz (Julius-Kühn-Archiv, 2014)
The production of carrots for the German market comes mainly from domestic production. To ensure the efficiency of chemical weed control and to minimize the damage of the crop a splitting of the recommended dosage up to three times is often practiced. Because of large field areas of the carrot cropping and processing enterprises, the potential to save herbicides by practicing an herbicide application adapted to the weed occurrence is high. The efficiency of a site-specific herbicide splitting on the late weed occurrence as well as on yield parameters was tested in field strip trials. Weed species and abundance were determined manually by raster sampling using a counting frame in spring before spraying. Afterwards in the three leaf growth stages of the carrots the weed coverage level was detected online using a camera sensor developed by the Leibniz Institute for Agricultural Engineering (ATB). Based on weed coverage level maps three application zones (200 L ha-1, 300 L ha-1, 400 L ha-1) were defined. On both sides of the site specific splitting strip a uniform splitting strip (400 L ha-1) was applied. The position of the application zones were the same during site-specific splitting at the second and third herbicide spraying respectively. Compared to a conventional uniform splitting herbicide savings were 16% (2005) und 20% (2006) at each spraying time. To evaluate the efficacy of the site-specific splitting on the yield manually harvesting were performed at opposite points in both treatments. The yield parameters fresh weight and numbers of carrots “total” and “marketable” were determined. Assuming a significance level of α = 5% the difference method for controlled treatment comparison in large scale field trials (t-test) resulted in 19 of the 24 tests in total no differences between the treatments. The late weed occurrence in both treatments was low.